2022
DOI: 10.1021/acs.jproteome.2c00069
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Consensus Spectrum Generation Methods in Proteomics

Abstract: Spectrum clustering is a powerful strategy to minimize redundant mass spectra by grouping them based on similarity, with the aim of forming groups of mass spectra from the same repeatedly measured analytes. Each such group of near-identical spectra can be represented by its so-called consensus spectrum for downstream processing. Although several algorithms for spectrum clustering have been adequately benchmarked and tested, the influence of the consensus spectrum generation step is rarely evaluated. Here, we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In general, highly similar spectra were compiled into a high-quality representative spectrum, which was considered a consensus spectrum. , One key aspect for creating a consensus spectrum is filtering the original spectra and clustering similar spectra. On examining the annotations derived from MN, the MS/MS spectra of NAAs (or STAs) were found to depend on the amino acid moiety, regardless of the fatty acyls (or bile acids) linked.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, highly similar spectra were compiled into a high-quality representative spectrum, which was considered a consensus spectrum. , One key aspect for creating a consensus spectrum is filtering the original spectra and clustering similar spectra. On examining the annotations derived from MN, the MS/MS spectra of NAAs (or STAs) were found to depend on the amino acid moiety, regardless of the fatty acyls (or bile acids) linked.…”
Section: Results and Discussionmentioning
confidence: 99%
“…24 Generally, highly similar spectra are compiled into a high-quality representative spectrum, which is considered as a consensus spectrum. 25 Generating consensus spectra is useful for visualizing clustering results, e.g., each MN node represents a precursor ion and the associated consensus spectrum compiled from several highly similar spectra. 12 It also helps the data-driven construction of spectral libraries, e.g., sophisticated spectrum clustering algorithms developed for data processing of proteomics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang et al reported using spectral clustering to reduce the runtime of subsequent peptide identification by over 50%. Third, the downstream analysis can achieve better results by operating on high-quality consensus spectra with a higher signal-to-noise ratio compared to the raw spectra …”
Section: Introductionmentioning
confidence: 99%
“…Third, the downstream analysis can achieve better results by operating on high-quality consensus spectra with a higher signal-to-noise ratio compared to the raw spectra. 10 Previous spectral clustering tools have focused on optimizing clustering quality and clustering speed. For example, MS-Cluster 5 and spectra-cluster 8 use an iterative greedy approach to efficiently merge similar spectra.…”
Section: Introductionmentioning
confidence: 99%